Seasonal variations of soil microbial biomass under different nutrient management and cropping systems on a Ferric Acrisol in Ghana - Logah, V; Ewusi - Mensah, N; Tetteh, E N; Quansah, C; Danso, I (Journal of Tropical Agriculture, 2013)
A study was conducted for three consecutive cropping seasons at the Central Agricultural Station, Kwadaso, Kumasi in the semi – deciduous forest zone of Ghana to investigate the seasonal variations of soil microbial biomass carbon, nitrogen and phosphorus under different nutrient management and cropping systems. The field experiment was a split–plot in a randomized complete block design replicated thrice. Continuous maize cropping (CM), maize/cowpea rotation (M/C) and maize/soybean intercropping (M/S) systems were considered as main plot factors. Poultry manure (PM) at a rate of 4 Mg ha–1, chemical fertilizer (CF) (NPK 15- 15- 15) at a rate of 90 - 60 - 60 kg ha–1, complementary application of poultry manure and chemical fertilizer (PM + CF) at 2 Mg ha–1 PM + 45- 30 -30 kg ha–1 CF and a control (no amendment) constituted the sub-plot factors. Biomass C showed increases over the seasons under nutrient management systems (amendments) and cropping systems. Values recorded in 2006- major rainy season differed significantly (P ≤ 0.05) from values recorded in the subsequent seasons. Unlike biomass C, biomass N recorded highest values in 2006 -minor rainy season. The lowest microbial P values were recorded in 2006 – minor rainy season which was characterized by P immobilization under all the amendments. Phosphorus was immobilized under cropping systems except in M/S system in the minor rainy season. Biomass carbon to nitrogen ratios (Cmic: Nmic) showed significant differences among amendments during all seasons of cropping and ranged from 3.9 – 35.0. Generally, cropping systems did not have siginificant effect on Cmic: Nmic ratios except in 2006- minor season when CM recorded the highest value of 15.2 with M/S system recording the least (11.9). Soil pH showed positive correlations with Cmic: Nmic ratios in the major rainy seasons but not in the minor season. The study has indicated that efficient seasonal nutrient management under cropping systems could result in buildup of microbial biomass C but may not necessarily lead to corresponding build up in biomass N and P. .